Organ-preserving approach via radiotherapy for small cell carcinoma of the bladder: an analysis based on the Japanese Radiation Oncology Study Group (JROSG) survey. (29th April 2019) - Akamatsu, Hiroko; Nakamura, Katsumasa; Ebara, Takeshi; Inaba, Koji; Itasaka, Satoshi; Jingu, Keiichi; Kosaka, Yasuhiro; Murai, Taro; Nagata, Kenji; Soejima, Toshinori; Takahashi, Shigeo; Toyoda, Tatsuya; et al.
Abstract: Small cell carcinoma of the bladder is extremely rare, accounting for <1% of all malignant tumours in the urinary tract. Thus, no standard therapy modality for this malignancy has been established. This study aimed to retrospectively analyse the clinical outcomes associated with definitive radiotherapy for small cell carcinoma of the bladder. A questionnaire-based survey of patients with pathologically proven small cell carcinoma of the bladder treated with definitive radiation therapy between 1990 and 2010 was conducted by the Japanese Radiation Oncology Study Group. The clinical records of 12 eligible patients were collected from nine institutions. The median age of the patients was 70.5 years (range: 44–87 years), and the median follow-up period was 27.3 months (range: 3.3–117.8 months). The median prescribed dose was 60 Gy (range: 50.0–61.0 Gy), and a median of 2.0 Gy (range: 1.2–2.0 Gy) was administered per fraction. Systemic chemotherapy combined with radiotherapy was performed in eight cases (66.7%). The 3- and 5-year overall survival rates were 50.0% and 33.3%, respectively. And the 3- and 5-year local control rates were 66.7% and 55.6%, respectively. Chemotherapy significantly improved overall survival and relapse-free survival ( P = 0.006 and 0.001, respectively). No serious adverse events occurred in the observation period. All patients who achieved local control maintained functional bladders. In conclusion, radiotherapy is a potential local treatment option and has an important role in maintaining quality of life. Systemic chemotherapy combined with local radiotherapy seems to be effective in improving survival.